Diagnostic and therapeutic appropriateness in bone and joint infections: results of a national survey. (3rd May 2016) - Esposito, Silvano; Russo, Enrico; De Simone, Giuseppe; Gioia, Renato; Petta, Ester; Leone, Sebastiano; Noviello, Silvana; Artioli, Stefania; Ascione, Tiziana; Bartoloni, Alessandro; Bassetti, Matteo; Bertelli, Davide; et al.
Abstract : The impact of infectious diseases (ID) specialist consultation in the management of many types of bacterial infections has been fully demonstrated but not for bone and joint infections (BJIs). Nineteen ID Italian centres collected of data from June 2009 to May 2012. Italian guidelines (2009) were used to determine the appropriateness of the diagnostic and therapeutic process of BJIs before and after consulting an ID specialist. Data on 311 patients were collected: 111 cases of prosthetic joint infection, 99 osteomyelitis, 64 spondylodiscitis and 37 fixation device infection. A significant increase of microbiological investigations, imaging techniques and blood inflammation markers were noted after consulting the ID specialist. Moreover, inappropriateness of treatment duration, dosage, and number of administrations significantly decreased after consultation. Infectious disease specialist intervention in the management of BJIs significantly increases the appropriateness both in performing instrumental and laboratory analysis, but especially in determining the correct therapy.